1998
DOI: 10.1002/(sici)1096-9071(199802)54:2<145::aid-jmv13>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

The use of semi-automated EBV IgG avidity determination for the diagnosis of infectious mononucleosis

Abstract: The diagnosis of acute Epstein-Barr virus (EBV) infection is based frequently on the combination of positive viral capsid antigen (VCA) IgM antibodies and negative EB viral nuclear antigen 1 (EBNA-1) IgG antibodies. However, both VCA IgM and EBNA-1 IgG can provide false positive and false negative results. Therefore, situations in which the EBV serology remains unclear are not uncommon. Determination of EBV IgG avidity can clarify the EBV status in these patients. So far, mainly immunofluorescence assays have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 34 publications
2
12
0
1
Order By: Relevance
“…In addition, the presence of IgM negativity resulting from inappropriate timing of blood sampling or the loss of EBNA antibodies owing to a suppressed immune system can obscure the identifi cation of primary infections or can lead to misdiagnosis. In such cases, it is suggested that the study of IgG avidity is critical to interpreting serological results correctly (9)(10)(11)(12). In general, the kinetics of affi nity maturation occurs in a couple of weeks; however, in some cases this maturation process may arise within three months after the onset of symptoms.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…In addition, the presence of IgM negativity resulting from inappropriate timing of blood sampling or the loss of EBNA antibodies owing to a suppressed immune system can obscure the identifi cation of primary infections or can lead to misdiagnosis. In such cases, it is suggested that the study of IgG avidity is critical to interpreting serological results correctly (9)(10)(11)(12). In general, the kinetics of affi nity maturation occurs in a couple of weeks; however, in some cases this maturation process may arise within three months after the onset of symptoms.…”
Section: Discussionsupporting
confidence: 47%
“…Moreover, the determination of specifi c IgG antibody avidity is performed thorough various techniques including agglutination, radioimmunoassay, complement fi xation, ELISA, immunofl uorescence, electroblotting, immunoblot (16). However, some studies suggest that immunoblot is easier to interpret, as compared to ELISA and is the preferred method for measuring avidity (12,21). Immunofl uorescence assay (IFA) is used widely for detecting EBV-specifi c antibodies because of its high sensitivity and specifi city.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to a mix of antigens, it is possible to use the whole or specific VCA (p23 or p18), IEA (ZEBRA), EA (p138 or p54) or EBNA (p72). Avidity varies depending on the kinetics of the various antibodies [63,66] , e.g. in VCA IgG, it has been reported that avidity is low in the samples collected during the first 12 wk after symptom onset, thus indicating recent infection [67] .…”
Section: Igg Aviditymentioning
confidence: 99%
“…Low concentrations of urea (e.g. 4.7M), however, have been used for showing low avidity IgG anti-EBV (Weissbrich 1998).…”
Section: Discussionmentioning
confidence: 99%